‘I consider myself to be a service provider’: Discursive identity construction of the forensic linguistic expert - Clarke, Isobelle; Kredens, Krzysztof (International Journal of Speech, Language and the Law, 2018)
This article reports on a research project investigating the professional identity of linguists as experts in legal and forensic settings. It reveals how they construct that identity discursively and intersubjectively. The analysis adopts a social constructionist perspective whereby the ways in which the experts talk and make sense of their professional experience are seen as identity building. Using interview data and the combined methodologies of corpus-assisted discourse studies (CADS) and thematic analysis (Braun and Clarke 2006), we identify a number of discursive resources the experts draw on. These include knowledge and expertise, professional and social duty, and aspects of their professional practice. At the same time, the experts construe their professional experience by reference to what they do not, and should not, do. We suggest that 'forensic linguist' is a shared identity with its own set of competencies, practices and obligations, although the profession is potentially still in development and/or is auxiliary to law enforcement.